Micro-CT imaging of breast tumors in rodents using a liposomal, nanoparticle contrast agent - Ehsan Samei (Dove Medical Press, 2009)
Ehsan Samei1,2,3,4, Robert S Saunders1, Cristian T Badea2,5, Ketan B Ghaghada2,5†, Laurence W Hedlund2,5, Yi Qi2,5, Hong Yuan6, Rex C Bentley7, Srinivasan Mukundan Jr2,3,5*1Carl E Ravin Advanced Imaging Laboratories, 2Department of Radiology, 3Department of Biomedical Engineering, 4Department of Physics, 5Center for In Vivo Microscopy, 6Department of Radiation Oncology, 7Department of Pathology, Duke University, Durham, NC, USA; †Current address: School of Health Information Sciences, University of Texas Health Science Center at Houston, Houston, TX, USA; *Current address: Department of Radiology, Brigham and Women’s Hospital, Boston, MA, USAAbstract: A long circulating liposomal, nanoscale blood pool agent encapsulating traditional iodinated contrast agent (65 mg I/mL) was used for micro-computed tomography (CT) imaging of rats implanted with R3230AC mammary carcinoma. Three-dimensional vascular architecture of tumors was imaged at 100-micron isotropic resolution. The image data showed good qualitative correlation with pathologic findings. The approach holds promise for studying tumor angiogenesis and for evaluating anti-angiogenesis therapies.Keywords: molecular imaging, liposome, angiogenesis, breast cancer, small animal imaging, micro-CT